Encouraging social acceptance of students with developmental disabilities in vocational school classes - Vujačić, Milja; Đević, Rajka (Studies in Teaching and Education, 2025)
The aim of this study is to examine how vocational high school teachers promote and enhance the social acceptance of students within the context of inclusive education. The sample consisted of 50 teachers from seven vocational high schools in Serbia, covering various fields of work. A questionnaire was used whereby the teachers were asked to describe the ways they encourage and improve the social acceptance of students with developmental difficulties. Qualitative thematic content analysis was used in the data processing, focusing on the following themes: the teachers' positive attitudes, support in the learning process, and the sensitisation of students. The findings indicate that the teachers recognise the importance of the social component of inclusive education, that their practices align with the key principles of this process, and that they successfully find solutions to the various challenges posed by inclusive teaching in order to achieve the desired outcomes. They nurture positive relationships with their students by unlocking their hidden potential, creating opportunities for learning and progress, and demonstrating a willingness to engage in professional development and collaboration. The teachers dedicate attention to student sensitisation through the development of social skills and the encouragement of prosocial behaviour. They apply cooperative learning, individualisation, and various motivational strategies in their teaching practice so as to stimulate cognitive progress and the social acceptance of individuals. It would be beneficial for schools and the educational system as a whole to encourage teachers to regularly share their experiences and tried-and-tested solutions in the inclusive education process through various forms of professional development, such as collaborative learning and cooperation. Future research in this field should involve a larger number of teachers, apply other qualitative methods such as interviews and focus groups, and include diverse stakeholders in order to gain a more comprehensive insight into teaching practices.
Keywords: inclusive education, teachers, vocational schools, encouraging social acceptance, teaching practice